The role of power in market control in supplier-buyer relations - Gharehdaghi, Mandana; Kamann, Dirk-Jan F. (Edelweiss Applied Science and Technology, 2024)
This study investigates the role of power dynamics in market control within supplier-buyer relationships, with a specific focus on blockchain technology adoption in supply chain networks. Using five focus group discussions, comprising of diverse participants categorized by sector, location, gender, and company size, the research explores how power influences decision-making processes. Findings reveal that larger companies often prioritize stability over innovation, limiting their willingness to adopt disruptive technologies like blockchain. In contrast, smaller firms demonstrate greater flexibility and openness to change. Beyond company size, factors such as product uniqueness, strategic network positions, and the personalities of decision-makers play critical roles in shaping blockchain adoption. Participants also reported persistent pressure from both suppliers and buyers to accept unfavorable terms, underscoring power imbalances that constrain smaller players. The analysis is framed within the conceptual structure of a model with a focus on the nuanced interplay of power and decision-making in the context of supply networks. Qualitative analysis of the discussions, conducted with Atlas.ti software, highlights the influence of sectoral differences, geographical variations, and gender dynamics in supply chain negotiations. This study provides valuable insights into the barriers and enablers of blockchain adoption within complex supply chain networks, emphasizing the critical interplay of power and communication in shaping market control.